Deborah A. Boehm: Intimate Migrations. Gender, Family, and Illegality among Transnational Mexicans.: New York and London: New York University Press 2012, 188 pp. - Souralová, Adéla (Lidé města, 2013)
A review of the book by Deborah A. Boehm.